1991
DOI: 10.1093/nar/19.23.6373
|View full text |Cite
|
Sign up to set email alerts
|

Operation of an efficient site-specific recombination system ofZygosaccharomyces rouxiiin tobacco cells

Abstract: Recombinase encoded by the R gene of pSR1 of Zygosaccharomyces rouxii mediates reciprocal recombination between two specific recombination sites (RSs) to induce excision or inversion of the DNA segment that is flanked by the RSs. We report here that site-specific recombination mediated by this system takes place effeciently in tobacco cells. To monitor the recombination events in tobacco cells, we have constructed two types of cryptic beta-glucuronidase reporter gene in such a way that recombination such as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(69 citation statements)
references
References 32 publications
1
68
0
Order By: Relevance
“…Deletions and inversions using the Z. rouxii R/Rs recombination system have been demonstrated in tobacco, Arabidopsis and rice (Onouchi et al, 1991;Toriyama et al, 2003). Here we have shown that the R/Rs system is also active in potato.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions and inversions using the Z. rouxii R/Rs recombination system have been demonstrated in tobacco, Arabidopsis and rice (Onouchi et al, 1991;Toriyama et al, 2003). Here we have shown that the R/Rs system is also active in potato.…”
Section: Discussionmentioning
confidence: 99%
“…rouxii contains a plasmid called pSR1 of 6251 bp which shows no homology with the S. cerevisiae 2W plasmid [9]. It has been extensively characterized especially for the recombinases Flp and R [10^14] and its ability to be active in heterologous backgrounds [15,16]. This paper reports the genomic analysis of strain CBS732 which contains seven chromosomes with sizes ranging from 1 to 2.75 Mb corresponding to an estimated total size of 12.8 Mb according to pulsed ¢eld gel electrophoresis determination [17].…”
Section: Introductionmentioning
confidence: 99%
“…PhiC31 integrase, which catalyzes unidirectional recombination between attP and attB sequences, has been used extensively for integration (27, 28) and cassette exchange (29,30), applications that take advantage of its nonreversibility. The R recombinase, a relative of FLP from the yeast Zygosaccharomyces rouxii (31, 32), has been shown to function in plants (33).In this report we describe the characterization of R and three other recombinases encoded by 2-μm circle-like plasmids of other yeasts. Although such plasmids are rare among yeasts, those characterized so far are very similar in structure to the 2-μm plasmid of S. cerevisiae (reviewed in ref.…”
mentioning
confidence: 97%
“…PhiC31 integrase, which catalyzes unidirectional recombination between attP and attB sequences, has been used extensively for integration (27,28) and cassette exchange (29,30), applications that take advantage of its nonreversibility. The R recombinase, a relative of FLP from the yeast Zygosaccharomyces rouxii (31,32), has been shown to function in plants (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation